Pengaruh Teman Sebaya Dan Lingkungan Keluarga Terhadap Pengambilan Keputusan Dalam Memilih Jurusan: ( Studi kasus pada Mahasiswa Jurusan manajemen Fakultas Ekonomi Universitas Majalengka ) - Nita Hernita (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2019)
This weaver was conducted in the students of Management majoring in economics Faculty of Majalengka University. The purpose of this research is to identify: peers, family environment and decision making, as well as how much influence of peers, the family environment to decision making. The object of this research is peer variables, family environment and decision making. The research population is the university's management student at Majalengka in 2013 – 2016. This research sample amounted to 87 students majoring in management Faculty of Economics, Majalengka University. The study was designed as a descriptive study of verificative with a quantitative approach. Hypothesis testing using T test testing and F test. Its analysis tools use multiple Regeresi analyses. Based on a hypothesis test the results of peers and family environments were significant to partial decision-making. Likewise, simultaneous peer-to-peer testing, the family environment has a positive and significant effect on decision making.